The Economic Incidence of Health Care Spending in Vermont - Eibner, Christine (RAND Corporation, 2015)
This report describes who ultimately pays for health care in Vermont by tracing spending back to the original funding source. The authors estimate the economic incidence of health spending in Vermont for 2012 and as projected for 2017.